Howard Elman's Farewell - Hebert, Ernest (Book collections on Project MUSE., 2014)
Part Falstaff, part King Lear, but all American, Howard Elman was a fifty-something workingman when he burst onto the literary scene in The Dogs of March, the first novel of the Darby Chronicles. Now in this, its seventh installment, the Darby constable is an eighty-something widower who wants to do "a great thing" before he motors off into the sunset. Maybe Howard achieves this goal, but he manages it in strange, wonderful, and dangerous ways. On his quest he's aided, abetted, hindered, and befuddled by his middle-aged children, his hundred-year-old hermit friend Cooty Patterson, a voice in his head, and the person he loves most, his grandson, Birch Latour. At 24, Birch has returned to Darby with his friends to take over the stewardship of the Salmon Trust and to launch a video game, Darby Doomsday. At stake is the fate of Darby. And the world? Maybe. Howard Elman's Farewell begins as a coming of (old) age story, morphs into a murder mystery, expands into a family saga, and in the end might just follow Howard Elman into the spirit world.